2012
DOI: 10.7205/milmed-d-11-00385
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Aeromedical Evacuation Does Not Affect Systemic Inflammation or Organ Injury in a Murine Model of Hemorrhagic Shock

Abstract: Hemorrhagic shock is a primary injury amongst combat casualties. Aeromedical evacuation (AE) of casualties exposes patients to a hypobaric, hypoxic environment. The effect of this environment on the host response to hemorrhagic shock is unknown. In the present study, we sought to determine the effect of simulated AE on systemic inflammation and organ injury using a murine model of hemorrhagic shock. Mice underwent femoral artery cannulation and were hemorrhaged for 60 minutes. Mice were then resuscitated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In severe trauma situations, hemorrhagic shock can accompany muscle injury or other types of tissue damage. Since hemorrhagic shock and/or tissue damage induce an inflammatory response 6,27,28 and hemorrhagic shock causes systemic hypoxia, 6 polytrauma likely drives splenic erythropoiesis. However, our understanding of the effect of polytrauma on splenic erythropoiesis is limited.…”
Section: Introductionmentioning
confidence: 99%
“…In severe trauma situations, hemorrhagic shock can accompany muscle injury or other types of tissue damage. Since hemorrhagic shock and/or tissue damage induce an inflammatory response 6,27,28 and hemorrhagic shock causes systemic hypoxia, 6 polytrauma likely drives splenic erythropoiesis. However, our understanding of the effect of polytrauma on splenic erythropoiesis is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Fluid resuscitation after HS can lead to ischemia/ reperfusion injury, which can trigger an excessive inflammatory response. [28] Macrophages play a crucial role in sensing and initiating the inflammatory response during H/R. [6,15,29] Our study demonstrated that the upregulation of HDAC6, Hsp90, and iNOS led to an increase in ROS levels in macrophages under H/R.…”
Section: Discussionmentioning
confidence: 66%
“…Using a rat model of polymicrobial sepsis, there were no significant changes in serum cytokine levels or mortality when rats were exposed to 8,000 ft hypobaria for 6 h, starting at 24 h postinjury (6). A similar exposure to hypobaria also had no significant effect in a mouse model of hemorrhagic shock (7). Nevertheless, exposure of lung-injured pigs to 8,000 ft hypobaria for 4 h resulted in greater pulmonary neutrophilic inflammation and micro-atelectasis compared with pigs maintained under anesthesia without exposure to hypobaria (8).…”
Section: Introductionmentioning
confidence: 91%